La gauche marocaine, défenseure du trône. Sur les métamorphoses d’une opposition institutionnelle - Abderrahim El Maslouhi (L’Année du Maghreb, 2009)
This article proposes analytical alternatives for comprehending the logic which underlies the political and identitary transformations of the USFP, one of the rare Arab socialist groups to “get down to business” after 40 years in opposition. The cooptation of the elites of the Moroccan social movement in a participatory or moderate position and their integration into the state’s social liberalism is as much a matter of political as it is of individual and collective survival. The gains produced as a result of such “rational choices” have produced unexpected results inversely proportional in terms of the “collective opposition capital” as well as the party’s ability to mobilize the left.